Agrarian reform: the reflection on the performance of the agrarian reform task force (GTRA) in the special region of Yogyakarta - Rohmat Junarto (Inovasi, 2022)
The aim of the agrarian reform program (RA) is to manage agrarian inequality and improve people's prosperity. The reflection on the performance of the RA Task Force (Gugus Tugas RA – GTRA) in each region is needed to accelerate the RA program nationally. Daerah Istimewa Yogyakarta (DIY) Province has a privilege in history, especially the authority to manage the Land of the Sultanate and Duchy (Tanah Kasultanan dan Kadipaten – TKK). Half-hearted knowledge about the content of RA, Local political will and a long history of land tenure have become problems in implementing the RA program in the regions. Therefore, this study aims to identify the performance of GTRA in DIY Province which is in charge of coordinating: the provision of land object of agrarian reform (Tanah Objek Reforma Agraria – TORA), implementation and integration of the RA program, as well as handling agrarian disputes/conflicts. The research method used is a case study. The result of this study is that asset management activities do not only target 'marginal' lands such as: oro-oro land, enclaves, Pangonan, cover, and structuring slums, but also TKK. Access management programs are carried out with local government programs such as: the development of the Pawonsari area (Pacitan-Wonogiri-Wonosari) and innovative movements in rural areas such as: G2R (Global Mutual Cooperation). However, the coordination, integration and synchronization of the RA program by these stakeholders has not been consolidated as outlined by the RA Presidential Decree. The results of this study are expected to provide improvements in the context of an increasing program by the National GTRA on behalf of RA, taking into account the basic needs of the community for the agrarian structure.